2014
DOI: 10.1681/asn.2013040433
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Activation of Signal-Regulatory Protein-α Stimulates Reactive Oxygen Species Production and Promotes Renal Ischemia Reperfusion Injury

Abstract: Ischemia reperfusion injury (IRI) causes tissue and organ injury, in part, through alterations in tissue blood flow and the production of reactive oxygen species. The cell surface receptor signal-regulatory protein-a (SIRP-a) is expressed on inflammatory cells and suppresses phagocytosis, but the function of SIRP-a in IRI has not been determined. We reported previously that the matricellular protein thrombospondin-1 is upregulated in IRI. Here, we report a novel interaction between thrombospondin-1 and SIRP-a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 69 publications
8
81
0
Order By: Relevance
“…Sharifi-Sanjani et al found that lack of CD47 provided protection from cardiac stress and alleviated heart failure [34]. TSP1 can not only regulate the CD47, but also can activate the Nox-1 receptor to increases superoxide in vascular and epithelial cells [35,36] Previous research shows that TSP-1 has an inflammatory-associated role in myocardial infarction and MIRI [37] The basic mechanism underlying the effect of CD47 blockade in alleviating MIRI was determined by several in vivo experiments demonstrating that limitation of the CD47/TSP1 signaling pathway can alleviate IRI by increasing eNOS-derived NO signaling. In liver and kidney I/R models, CD47 knockout mice were found to suffer less damage compared to control mice after periods of vascular occlusion followed by recanalization [13,17].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…Sharifi-Sanjani et al found that lack of CD47 provided protection from cardiac stress and alleviated heart failure [34]. TSP1 can not only regulate the CD47, but also can activate the Nox-1 receptor to increases superoxide in vascular and epithelial cells [35,36] Previous research shows that TSP-1 has an inflammatory-associated role in myocardial infarction and MIRI [37] The basic mechanism underlying the effect of CD47 blockade in alleviating MIRI was determined by several in vivo experiments demonstrating that limitation of the CD47/TSP1 signaling pathway can alleviate IRI by increasing eNOS-derived NO signaling. In liver and kidney I/R models, CD47 knockout mice were found to suffer less damage compared to control mice after periods of vascular occlusion followed by recanalization [13,17].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…Similarly, TSP1-mediated increases in superoxide were abated in VSMCs treated with NADPH oxidase 1 (Nox1) siRNA or in aortic rings from Nox1 -/-mice but not in cells treated with control siRNA or in aortic rings from WT mice. In renal tubular epithelial cells, TSP1 also increased Nox1-derived superoxide levels and this involved interaction with SIRPa (307). Superoxide levels represent a balance between enzymatic production and catabolism by SOD.…”
Section: B Tsp1 and Ros Signaling In Vascular And Renal Cellsmentioning
confidence: 93%
“…TSP1 (2.2 nM) decreased NOmediated vasodilation of aortic rings from WT and Thbs1 -/-mice but not Cd47 -/-mice (11). Treatment of WT murine vessels with the membrane-permeable superoxide scavenger 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (Tempol) partially reversed the inhibitory actions of TSP1 (307). Tempol can inhibit the Fenton reaction, a source of hydroxyl radical that limits arterial vasodilation (263).…”
Section: B Tsp1 and Ros Signaling In Vascular And Renal Cellsmentioning
confidence: 99%
See 2 more Smart Citations